SPC25 upregulates CCND1 to promote the progression of esophageal squamous cell carcinoma by inhibiting MDM2-mediated E2F1 ubiquitination - Haoyao Jiang; Xiangfeng Jin; Haiyong Gu; Bin Li; Zhigang Li; Yifeng Sun (Translational Oncology)
Esophageal squamous cell carcinoma (ESCC) is highly malignant worldwide. Despite significant advances in the treatment of ESCC, the prognosis remains unfavourable, necessitating research into its mechanisms and treatments. Spindle component 25 (SPC25) can ensure the fidelity of mitotic progression and the accurate segregation of chromosomes, thus plays an important role in the development of malignant tumors, but its role in ESCC is yet to be determined. In this study, the expression of SPC25 was assessed by IHC in 88 primary ESCC samples, with its expression being correlated with advanced clinical features. The function of SPC25 in the proliferation, migration and tumorigenicity of ESCC cells was verified in vitro and in vivo. Mechanistically, SPC25 facilitated tumorigenesis through promoting CCND1 expression. As the transcription factor for CCND1, E2F1 is stabilized by SPC25 through binding the ubiquitin ligase MDM2, resulting in enhanced E2F1 expression, which in turn promotes the expression of CCND1. In addition, overexpression of CCND1 counteracted the effects of SPC25 silencing. Collectively, we demonstrated that the aberrant expression of SPC25 inhibited E2F1 ubiquitination and promoted CCND1 expression, thus accelerating the progression of ESCC. These findings propose novel insights into the role of SPC25 in ESCC and provide potential therapeutic strategies for targeting SPC25 in ESCC patients.